Qualitative Phytochemical Screening of Ethanolic Extract of Ocimum basilicum L. Leaves - Bahri, Syamsul; Wirdullutfi, Wirdullutfi; Hijriani, Baiq Isti (Jurnal Biologi Tropis, 2025)
Ocimum basilicum L. (basil) leaves are widely recognized for their potential bioactive compounds. This study aimed to qualitatively evaluate the phytochemical constituents of ethanolic extracts of basil leaves. Dried basil leaves were extracted using 96% ethanol, and the resulting extract was subjected to standard phytochemical screening tests to identify major secondary metabolites. The results revealed a strong presence of alkaloids and steroids, indicating that these compounds are dominant constituents in the ethanolic extract. In addition, flavonoids, tannins, and phenolic compounds were detected at lower intensities, suggesting their presence in smaller amounts. Conversely, terpenoids and saponins were not detected in the extract. These findings indicate that ethanol is an effective solvent for extracting alkaloids and steroids from basil leaves, while its efficiency for terpenoids and saponins may be limited. The presence of these secondary metabolites supports the potential biological activity of Ocimum basilicum leaves and provides a scientific basis for further studies on their pharmacological and biological activities.